Penyingkapan Diri Ibas Yudhoyono Dalam Instagram Dan Reaksi Ani Yudhoyono Terhadap Postingan Instagram Ibas - Suzy Azeharie; Wulan Purnama Sari (Jurnal Komunikasi, 2015)
AbstrackEdy Baskoro Yudhoyono’s or well known as Ibas is the youngest son of the former President SBY and currently active as a politician for Democratic Party and member of Parliament. Thus it is important for Ibas as a political actor to do self-disclosure and convey political messages through his social media accounts. The main object of this paper is Ibas’s post in his Instagram account as a media for unveiling himself. This paper will also discuss about Mrs. Ani Yudhoyono or Ibas’s mother, the former first lady, in given response and reaction on the Ibas’s post. Methodology used for data collection in this paper is content analysis. The results of the content analysis show that Ibas was frequently post pictures of his family than his political activities. Moreover Ibas himself never respond to all incoming comments from his followers. Eventhough it was positive comments. Surprisingly, reaction and response was given by Mrs. Ani Yudhoyono. In many of Ibas’s post, Mrs. Ani Yudhoyono was sharp and yet keen on responding to the comments coming from Ibas’s followers. Mrs. Ani Yudhoyono response was often received disapproval and negative comments from other followers, because to their concern Mrs. Ani Yudhoyono was not using the right grammar of English and this eventually led to a hot debate between fellow follower's comments. The final conclusion that can be obtained is Ibas did not make his Instagram account as a media unveiling herself but only using his account as a medium for sharing photos. Which appear to be more active in doing communication and self-disclosure is Mrs. Ani Yudhoyono herself.AbstrakEdy Baskoro Yudhoyono atau lebih dikenal dengan nama Ibas merupakan putra bungsu dari mantan presiden SBY dan saat ini aktif sebagai politikus Partai Demokrat dan juga anggota DPR RI. fokus utama dalam penelitian ini adalah postingan Ibas dalam akun instagramnya yang merupakan sarana untuk penyingkapan dirinya, serta bagaimana reaksi Ibu Ani Yudhoyono mengenai postingan-postingan Ibas tersebut. Metode pengumpulan data yang digunakan dalam penelitian ini adalah analisis isi. Berdasarkan hasil analisis isi yang dilakukan diperoleh hasil bahwa Ibas lebih sering melakukan posting tentang keluarganya daripada mengenai kegiatan politiknya. Selain itu Ibas tidak pernah sekalipun merespon semua komentar yang masuk dari para follower-nya, baik itu komentar baik ataupun mencela. Respon aktif justru diberikan oleh Ibu Ani. Ibu Ani memberikan komentar dalam bahasa inggris untuk merespon komentar-komentar yang masuk kedalam postingan Ibas. Respon Ibu Ani ini seringkali mendapat celaan dari para follower lainnya, karena dianggap tidak sesuai dengan tata bahasa inggris dan pada akhirnya berujung pada perang komentar antar sesama follower. Kesimpulan akhir yang dapat diperoleh adalah Ibas tidak menjadikan akun instagram sebagai media penyingkapan dirinya, instragram hanya digunakan Ibas sebagai media untuk berbagi foto, dan yang tampak aktif melakukan komunikasi dan penyingkapan diri adalah Ibu Ani.